Analysis of the Physical and Mental Workload of Nurses with the Implementation of Patient Safety During the Covid-19 Pandemic - Abubakar Betan; Zaenal; Hamzah; Abdullah; Hilmiah (Postgraduate, University of Mataram, 2023)
The workload of nurses in hospitals encompasses both physical and mental aspects. Physical tasks include tasks such as lifting patients, administering infusions, monitoring vital signs, and administering oxygen, among others. Meanwhile, mental workload involves dealing with job complexity, providing mental and emotional support to patients and their families, especially those undergoing operations or in critical condition, employing specialized skills in patient care, and establishing effective communication with patients and their families. This study aims to examine the physical and mental workload of nurses in relation to the implementation of patient safety during the COVID-19 pandemic at Labuan Baji Hospital in Makassar. The research design employed a quantitative approach with a cross-sectional design, and the study sample consisted of 36 respondents. The objective of this study is to explore the relationship between the independent variables (mental workload and physical workload) and the dependent variable (implementation of patient safety). The study findings reveal a p-value of 0.409 for the relationship between physical workload and the implementation of patient safety, and a p-value of 0.069 for the relationship between mental workload and the implementation of patient safety. In conclusion, this study does not find a significant relationship between physical workload and the application of patient safety in the inpatient ward of Labuan Baji General Hospital in Makassar. Additionally, no significant relationship is observed between mental workload and the implementation of patient safety in the same setting. The results of this study contribute to enhancing understanding of patient safety within hospitals and its association with the workload of nurses.